2018
DOI: 10.1021/acssuschemeng.8b05599
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of 2D Covalent-Organic Framework Membranes for Organic Solvent Nanofiltration

Abstract: Covalent-organic frameworks (COFs) are ordered crystalline materials covalently formed by building blocks of light elements. There has been increasing interest in the development of COF membranes for chemical separation. In this study, seven two-dimensional (2D) COF membranes are computationally designed with different functional groups and aperture sizes. By 245 sets of molecular simulations, the seven ultrathin COF membranes are investigated for organic solvent nanofiltration (OSN) of seven solvents (acetoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…COFs with rich secondary amine groups have also been synthesized by interfacial polymerization to improve the ethanol permeance . A computational study was also used to unravel the key governing factors of solvent permeation and solute rejection in COF membranes . The solvent permeances were correlated with different combinations of solvent properties in the hydrophilic and hydrophobic membranes; the rejection was governed by the complex interplay of membrane functionality, solute size and polarity, solvent viscosity, solute–solvent interaction, and pore size.…”
Section: Environmental Treatmentmentioning
confidence: 99%
“…COFs with rich secondary amine groups have also been synthesized by interfacial polymerization to improve the ethanol permeance . A computational study was also used to unravel the key governing factors of solvent permeation and solute rejection in COF membranes . The solvent permeances were correlated with different combinations of solvent properties in the hydrophilic and hydrophobic membranes; the rejection was governed by the complex interplay of membrane functionality, solute size and polarity, solvent viscosity, solute–solvent interaction, and pore size.…”
Section: Environmental Treatmentmentioning
confidence: 99%
“…[14][15][16] Recent simulation studies have revealed that the COF nanopores offer fast transport pathways. [17][18][19] Considerable research progress has been devoted to the synthesis of COF membranes recently. Banerjee et al reported a group of b-ketoenamine based COF structures that have shown unpredictable chemical stability not only in organic solvents but also in aqueous, acidic and basic media.…”
Section: Introductionmentioning
confidence: 99%
“…A simulation work has been conducted to guide the selection of COF materials for OSN and explore the factors affecting the OSN performance of COF membrane. [204] Seven types of singlelayered TpPa-X membranes with different apertures (5.2-7.6 Å) and hydrophilicity were computationally designed by introducing different functional groups. The permeances of some solvents, such as acetonitrile, methanol, ethanol, acetone, isopropanol (IPA), and methyl ethyl ketone (MEK), are regulated by the pore size and membrane functionality, while the flux of n-hexane is determined merely by the aperture because of the relatively weak interaction between the membrane and the solvent (Figure 27a).…”
Section: Organic Solvent Nanofiltrationmentioning
confidence: 99%